SPECTROSCOPIC EVIDENCE FOR PRESSURE-INDUCED PHASE TRANSITIONS IN DIOPSIDE - Chopelas A.; Serghiou G. (My University, 2002)
Raman spectra of diopside were collected from atmospheric pressure to 71 GPa. The pressure dependences of 22 modes were determined. Changes occurred in the spectra at three different pressures. First, at approximately 10 GPa, the two Raman modes at 356 and 875 cm-1 disappeared, while the mode at 324 cm-1 split into two modes, diverging at this pressure with significantly different pressure shifts; second, at approximately 15 GPa, a small (1 to 2 cm-1) drop in several of the frequencies was observed accompanied by changes in the pressure dependency of some of the modes; and third, above 55 GPa, the modes characteristic of chains of tetrahedrally coordinated silicon disappeared, while those for octahedrally coordinated silicon appeared. The first change at 10 GPa appears to be a C2/c to C2/c transition involving a change in the Ca coordination. The third change above 55 GPa appears to be a change in the silicon coordination. At 15 GPa, it is suggested that a change in compressional mechanism takes place.
Keywords: DIOPSIDE; CLINOPYROXENE; RAMAN SPECTROSCOPY; HIGH PRESSURE